Drogas e ambiente de trabalho : um olhar a partir do estudo realizado em uma empresa pública de Mato Grosso - Pultrini, Adalisa Martins Marques (2015)
Currently, drug use has become a matter of public health and safety, in view of the increased consumption, drug trafficking and the various consequences and injuries. Recent studies conducted in Brazil and the Central West region show high proportion of drug use in the population; however, there are few studies on this subject targeting the audience / the workers / as. In this sense, the present study aimed to reflect on the theme drugs and working environment, from the study next to / the employees / the charts and Orders Treatment Centre - ETSC of Mato Grosso Post on current consumption psychoactive substances and its relation to the issue of gender, work and major related risk factors. To that end, we conducted field research and structured interview through a questionnaire with closed questions, with a sample of 45 employees / as. In the survey, it was found that alcohol is the drug of greatest use among / the respondents / 20% and the consumption are considered risk and 6.66% are harmful or likely to alcoholism use, and the second drug most consumed are psychoactive drugs (26.66%), particularly muscle pain killers / relaxing and diet pills, especially among women, noting also that there is a difference in the type of drugs and consumption pattern held between men and women, higher consumption by men. Between / the respondents / as, there was no claim of tobacco consumption and current drug considered illegal, only affirmation of use in their lifetime marijuana, however, 20.82% said they have experienced problems related to consumption drugs, particularly situations of violence, accidents and drunk driving. In the present study also researched the aspects related to drug use and age, religion and social relations, as well as the current public policy on drugs in Brazil, from the relationship between drugs, Capital and Labor. Certainly, this study may contribute to the development of drug policies and programs in correios that meet the needs found in social reality researched, as well as to other employees / as and health organizations in the country, focusing on the comprehensive health care, improving the conditions of life and work and the prevention of abuse and dependence on alcohol and other drugs in the workplace.